Experimental investigation and computer simulation of the magnetron sputtering device with two erosion zones - Bogdanov, R.V.; Kostiukevych, O.M. (Вопросы атомной науки и техники, 2013)
There was built the self-consistent computer model of the magnetron sputtering device with two erosion zones of cathode-target, based on Monte Carlo algorithm. The magnetron sputtering device is an additional module for the industrial vacuum system VUP-5. The results of computer simulation and the experimental data from test targets sputtering on this magnetron sputtering device demonstrated their compliance in the identical conditions. Построена самосогласованная компьютерная модель магнетронного распылительного устройства с двумя зонами эрозии катода-мишени. Использовался алгоритм Монте-Карло. Магнетронное распылительное устройство является дополнительным модулем для промышленной вакуумной установки ВУП-5. Сравнение результатов компьютерного моделирования и экспериментальных данных распыления тестовых мишеней на данном магнетронном распылительном устройстве продемонстрировало их соответствие при одинаковых условиях. Побудована самоузгоджена комп’ютерна модель магнетронного розпилювального пристрою з двома зонами ерозії катода-мішені. Використовувався алгоритм Монте-Карло. Магнетронний розпилювальний пристрій є додатковим модулем для промислової вакуумної установки ВУП-5. Порівняння результатів комп’ютерного моделювання та експериментальних даних розпилення тестових мішеней на даному магнетронному розпилювальному пристрої продемонструвало їх відповідність за однакових умов.